2019
DOI: 10.1590/s0004-2803.201900000-31
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Aripiprazole on Mkn45 and Nih3t3 Cell Lines and Genotoxic Effects on Human Peripheral Blood Lymphocytes

Abstract: BACKGROUND: Gastric cancer is known as the fourth most common cancer. Current treatments for cancer have damaged the sensitive tissues of the healthy body, and in many cases, cancer will be recurrent. Therefore, need for treatments that are more effective is well felt. Researchers have recently shifted their attention towards antipsychotic dopamine antagonists to treat cancer. The anticancer activities of aripiprazole remain unknown. OBJECTIVE: This study aimed to evaluate the efficacy and safety of aripipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In fact, as a outcome of hyperglycemia, diabetic patients are at augmented risk for comorbid conditions affecting different organs. One of the main effects of diabetes is the impairment of self-repairing abilities and resistance to existing wound management [50].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, as a outcome of hyperglycemia, diabetic patients are at augmented risk for comorbid conditions affecting different organs. One of the main effects of diabetes is the impairment of self-repairing abilities and resistance to existing wound management [50].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, epidemiological observations have indicated that schizophrenia patients exhibited low risk of cancer after long-term drug treatment, which has potential as anticancer agents. Some antipsychotic agents like chlorpromazine, thioridazine, aripiprazole and clozapine have been shown anticancer activity [16]. Secondly, Jahrami et al found that a pro-inflammatory diet is associated with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…The IC 50 value taken from ref. [ 81 ]. K D = 60 ± 2.8 pM ( n = 6); B MAX = 2.0 ± 0.1 pmol/mg ( n = 6).…”
Section: Figures Scheme and Tablesmentioning
confidence: 99%